Analysis Of Efficiency Of Technical And Factors Affecting In Aromatic Rice Farming In The Seluma Regency - Maheran Mulyadi; Ketut Sukiyono; Sriyoto Sriyoto (Journal of Agri Socio Economics and Business, 2021)
The research objective is to determine the level of technical efficiency and the factors that influence the level of technical inefficiency, to analyze the relationship between input and output in the production process of aromatic rice farming in Seluma regency.Total number of respondents were 73 farmers who planted Aromatic rice. The Cobb Douglass of Frontier Stochastic approach was used, whereas for the factors that influence the inefficiency function as the initial answer of the above analysis results of the production function parameter were obtained through the Maximum Likelihood Estimation (MLE), with an LR value of 14.3620 which was higher than t table 99% (2.39). It had a significant effect on the 99% confidence level. It was seem that, there was no meaning that all aromatic rice farmers in the regency were 100% efficient. It could be seen that the MLE log-likelihood value of 29.9157 was higher than the OLS log-likelihood value of 22.7347. The lowest technical efficiency value was achieved by the farmers by 0.55 and the highest by 0.97.  In the research area, the majority of the use of production factors was efficient, from 73.34% already in the value of efficiency between 0.90-1.00, meaning that 73.34% had approached the maximum efficiency. The result of the disseminated coefficient (R2) of 0.277 could mean a significant effect of 27.7 percent on the inefficiency variable while the remaining 72.3 percent is influenced by other factors not included in this research variable.